Molecular Characterization of Plasmid-Mediated Quinolone Resistance Genes in Multidrug-Resistant Isolated From Wastewater Generated From the Hospital Environment - Omowunmi A. Banjo; Abimbola O. Adekanmbi; Oluwatimileyin J. Akinbola; Benjamin T. Thomas; Olusolape A. F. Ilusanya (Environmental Health Insights)
Aim: This study investigated the carriage of Plasmid-Mediated Quinolone Resistance (PMQR) genes in fluoroquinolone-resistant Escherichia coli recovered from wastewater generated by healthcare institutions. Materials and Methods: Isolation of fluoroquinolone-resistant Escherichia coli was done on medium supplemented with 1 µg/mL of ciprofloxacin (a fluoroquinolone). Presumptive isolates were identified via the detection of uidA gene. Susceptibility of the isolates to a panel of antibiotics was done using disc diffusion method. Detection of PMQR genes in the isolates was done using primer-specific PCR. Results: Thirty fluoroquinolone-resistant Escherichia coli were obtained from the wastewater over a period of 6 months. The resistance to each of the antibiotic tested was: ampicillin (100%), ceftriaxone (100%), nalidixic acid (100%), tetracycline (96.7%), cefotaxime (96.7%), amoxicillin-clavulanate (80%), gentamicin (60%), cefoxitin (30%), and imipenem (3.3%). The Multiple Antibiotic Resistance Index (MARI) ranged from 0.6 to 0.9. The detection of PMQR genes in the 30 isolates was: qnrA (76.7%), qnrB (53.3%), qnrS (63.3%), aac(6′)-lb-cr (43.3%), and qepA (43.3%). All the fluoroquinolone-resistant Escherichia coli carried at least one PMQR determinant. Conclusion: This study revealed that untreated hospital wastewaters are significant hub of multidrug-resistant and fluoroquinolone-resistant Escherichia coli , showing high carriage of PMQR genes, and may be a major contributor to the resistome of fluoroquinolone-resistant bacteria in the Nigerian environment.